2006
DOI: 10.1099/vir.0.81754-0
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxic-response elements in the oncolytic parvovirus Minute virus of mice do not allow for increased vector production at low oxygen concentration

Abstract: Vectors derived from the autonomous parvovirus Minute virus of mice, MVM(p), are promising tools for the gene therapy of cancer. The validation of their in vivo anti-tumour effect is, however, hampered by the difficulty to produce high-titre stocks. In an attempt to increase vector titres, host cells were subjected to low oxygen tension (hypoxia). It has been shown that a number of viruses are produced at higher titres under these conditions. This is the case, among others, for another member of the family Par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…While one study showed that GADD34 expression (induced by hypoxia in our study) impairs replication of vesicular stomatitis virus,30 an RNA virus, another study argued that hypoxia does not affect vesicular stomatitis virus replication, using indirect evidence in the form of viral replication in hypoxic areas of a tumor 31. Hypoxia has also been shown to inhibit the replication of the oncolytic DNA virus, Minute virus of mice 32. Further, hypoxia has been demonstrated to inhibit the replication of other DNA viruses that have not yet been used as oncolytic viruses, such as simian virus 40 (ref.…”
Section: Discussionmentioning
confidence: 51%
“…While one study showed that GADD34 expression (induced by hypoxia in our study) impairs replication of vesicular stomatitis virus,30 an RNA virus, another study argued that hypoxia does not affect vesicular stomatitis virus replication, using indirect evidence in the form of viral replication in hypoxic areas of a tumor 31. Hypoxia has also been shown to inhibit the replication of the oncolytic DNA virus, Minute virus of mice 32. Further, hypoxia has been demonstrated to inhibit the replication of other DNA viruses that have not yet been used as oncolytic viruses, such as simian virus 40 (ref.…”
Section: Discussionmentioning
confidence: 51%
“…Hypoxia (1% O 2 ) induces lytic replication of EBV [92] and Kaposi sarcoma-associated herpesvirus [93], but suppresses replication of oncolytic parvovirus Minute virus of mice [94], adenovirus [95] or Moloney murine leukemia virus [96]. Primary T cells cultured at 3–6% O 2 maintain an intracellular redox environment similar to the in vivo situation, as opposed to T cells cultured at atmospheric 21% O 2 , in which the intracellular redox state is significantly altered [97].…”
Section: Effect Of Hypoxia On Hiv-1mentioning
confidence: 99%
“…The two features of tumor cells that attract parvoviruses are mitosis and hypoxia. The environment ruled by hypoxia--inducible transcription factor-α and hypoxia-responsive element favors parvovirus replication [338]. The oncotropic oncoselective minute viruses of mice (MVMi and prototype MVMp) replicate in human tumor cells in vitro without displaying any pathogenicity in the human host.…”
Section: Myxomavirusmentioning
confidence: 99%